Complete Genome Sequence of the Temperate Klebsiella pneumoniae Phage KPP5665-2 - Carl, Gaby (Genome Announc, 2017)
We describe here the genome sequence of the novel temperate Klebsiella pneumoniae phage KPP5665-2 isolated from a Klebsiella pneumoniae strain recovered from milk in Germany in 2016. The phage exhibited a narrow host range and a siphoviridal morphology. KPP5665-2-related prophage sequences were detected in whole-genome sequencing (WGS) data of various Klebsiella species isolates.